The Historical Values of Islamic Education and Islamic Law in the Culture of the Nusantara: An Analysis of Their Implementation and Relevance in Contemporary Society - Hairuddin Cikka; Muhammad Fatur Afriansyah; Mahmuda Bin Harun Rasyid (Published by Institut Teknologi Pendidikan Indonesia, 2026)
The research findings indicate that Islamic education in the Archipelago has developed through traditional institutions such as pesantren, surau and dayah, which play a vital role in shaping the character, morals and spirituality of the community. The historical values that emerge within this educational system include good manners, sincerity, simplicity, tolerance and mutual cooperation. Meanwhile, Islamic law in the Nusantara has developed adaptively through a process of acculturation with customary law, resulting in a legal system that is moderate, flexible and contextual. This research also found that the integration of Islamic education and Islamic law plays a vital role in shaping a harmonious social order within the Muslim communities of the Nusantara. In the context of contemporary society, these historical values remain relevant as a foundation for strengthening character education, religious moderation, and the formation of an inclusive society amidst the challenges of globalisation and modernisation. It can therefore be concluded that the historical values of Islamic education and Islamic law within the culture of the Nusantara not only hold historical significance but also make a significant contribution to building a social and educational system relevant to the modern era.